A case for the study of native extracellular vesicles - Nambiar, Dhanya; Le, Quynh-Thu; Pucci, Ferdinando (Frontiers in Oncology, 2024)
Three main areas of research revolve around extracellular vesicles (EVs): their use as early detection diagnostics for cancer prevention, engineering of EVs or other enveloped viral-like particles for therapeutic purposes and to understand how EVs impact biological processes. When investigating the biology of EVs, it is important to consider strategies able to track and alter EVs directly in vivo, as they are released by donor cells. This can be achieved by suitable engineering of EV donor cells, either before implantation or directly in vivo. Here, a case for the study of native EVs is made, that is, EVs released by cells living within a tissue. Novel genetic approaches to detect intercellular communications mediated by native EVs and profile recipient cells are discussed. The use of Rab35 dominant negative mutant is proposed for functional in vivo studies on the roles of native EVs. Ultimately, investigations on native EVs will tremendously advance our understanding of EV biology and open novel opportunities for therapy and prevention.